Hubungan Kerja Shift Malam dan Kejadian Kanker Payudara Pada Pekerja Wanita: Tinjauan Kasus Berbasis Bukti - Ayu Munawaroh; Fakhrul Razan (Universitas Ngudi Waluyo, 2020)
Within the last decade, shift work has been an important issue, because it can give negative impacts to the worker’s body. International Agency for Research on Cancer (IARC) on 2007 had classified the shift work which disturb circadian rhythm as probably carcinogenic. One of the cancer which often been researched is breast cancer. Moreover, Around 572% of female workers are in professional and service sector that closely related to night shift work. This evidence based case report aims to know the relation between night shift work and breast cancer in female workers. Based on electronic database literature searching on September 26th 2018 using PubMed, EBSCo (MEDLINE with fulltext), and ProQuest, there are seven meta-analysis which useful to be critically appraised. The result of critical appraisal was increased risk of breast cancer in night shift female workers. Therefore, there was a sufficient validity with number needed to harm by 15 people. It can be concluded that night shift work, with duration and certain period could be risk factor for breast cancer in female workers, then further approaches are needed regarding this matter.